Transesterification of crude palm oil adsorbed on spent bleaching clay and catfish oil using CaO and ZnO as catalysts - Intan Shafinaz, Abd Manaf (2016)
In the present work, the transesterification of crude palm oil (CPO) adsorbed on spent bleaching clay (SBC) and waste catfish fat using Commercial-CaO, barnacle (B-CaO) and mixed-oxide (B-CaO·ZnO) as a heterogeneous catalyst were attempted. In order to enhance the catalytic activity, the catalysts have been calcined at 500 - 900 °C for 2 h. It have been had found 900 °C is the optimum condition for catalyst preparation because upon calcination, the catalyst transformed to CaO from the initial CaCO3 structure. The mechanochemical treatment had been used for preparation of mixed oxide. The catalyst had been characterized using thermogravimetric/differential thermal analysis (TGA/DTA), x-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Brunauer, Emmett and Teller surface area (BET), x-ray fluorescence (XRF), field emission scanning electron microscopy (FESEM), energy-dispersive x-ray spectroscopy (EDX) and basic strength using Hammett indicators. Results showed that the CaO exist at the optimum condition of calcination and also found that these catalyst consist of strong basic site. The result shows that, the optimal condition for transesterification of catfish fat and SBC reaction catalyzed by B-CaO at 93.7% and 94.0%, respectively in 4 h reaction duration at 65 °C, methanol to oil molar ratio at 12:1 and 5 wt. % catalysts as an optimal reaction conditions. On the other hand, by using B-CaO·ZnO as catalyst for SBC oil and catfish fat, the optimal conditions were found to be 3 wt.% catalyst, 9:1 methanol to oil molar ratio, yielding 94.7% and 96.3% ME, respectively for 4 h and 2 h of reaction duration at 65 °C. In addition, in-situ transesterification using SBC also been carried out where the optimal conditions were found to be 15 wt.% and 25 wt.% of catalyst, 110:1 and 150:1 methanol to oil molar ratio resulting ME content for BCaO ·ZnO and B-CaO, respectively in 6 h and 8 h duration at 65 °C. The catalysts (BCaO and B-CaO·ZnO) can be reused up to four times maintaining ME content of 65% and 70%, respectively. The methyl esters produced were found to confirm mainly the key specifications of biodiesel. The engine performance of SBC B5 was investigated on a single cylinder 4-stroke diesel engine (YANMAR NF19-SK). The results indicated that the SBC B5 gave lower CO2 emission compared to neat diesel, thus contributed to the reduction of greenhouse gases. The barnacle shells as a source of calcium oxide can be widely applied as it is or mixed with other oxides as a catalyst in biodiesel production.